The efficacy of fascia iliaca compartment block for pain control after hip fracture: A meta-analysis - Hong, Hui-kan (Medicine (Baltimore), 2019)
BACKGROUND: To assess the effect of fascia iliaca compartment block (FICB) on pain control and morphine consumption in patients with hip fracture. METHODS: We searched databases (PubMed, Embase, Cochrane Library) for eligible randomized controlled trials (RCTs) published prior to September 12, 2018. We only included hip fracture patients who received FICB versus placebo for pain control. Risk ratios (RRs), standard mean differences (SMD) and 95% confidence intervals (CI) were determined. Stata 12.0 was used for the meta-analysis. RESULTS: Eleven trials involving 937 patients underwent hip fracture were retrieved. FICB significantly decreased the pain intensity at 1–8 h (SMD = −1.03, 95% CI [−1.48, −0.58], P = .000), 12 h (SMD = −1.06, 95% CI [−1.36, −0.75], P = .000), 24 h (SMD = −1.14, 95% CI [−1.66, −0.62], P = .000) and 48 h (SMD = −0.96, 95% CI [−1.33, −0.60], P = .000). Moreover, FICB could reduced the total morphine consumption and the occurrence of nausea (P < .05). There was no significant difference between the pain intensity at 72 h (SMD = 0.11, 95% CI [−0.12, 0.34], P = .355). CONCLUSIONS: FICB has a beneficial role in reducing pain intensity and morphine consumption after hip fracture. Moreover, FICB has morphine-sparing effects when compared with a control group. More high-quality RCTs are needed to identify the optimal technique and volume of injectate for FICB.